Does Market Power or Efficiency affect the performance of the Brazilian banking sector? - Pilava, Andrea (2014)
This paper provides an empirical analysis of market concentration in the Brazilian banking sector. The descriptive analysis indicates that the Brazilian banking sector is highly concentrated following an era of deregulation, mergers and acquisitions, privatisations and foreign investment. Hence, the empirical part of this paper takes into account, in particular, it’s highly concentrated structure. This analysis follows Berger’s (1995) model on market concentration by testing the market power (Structure-Conduct-Performance and Relative Market Power) and efficient structure(X-and Scale Efficiency) hypotheses in relation to the banks’ profitability. Moreover, the Data Envelopment Analysis technique will be adopted for obtaining reliable efficiency measures for latter hypothesis. Using a balanced panel of 12 Brazilian banks between 2005 and 2013, this paper shows that the Scale Efficiency Hypothesis explains the supernormal profits of Brazilian banks. Besides this finding, the capitalisation, liquidity and GDP growth determinants were found to have a significant relationship with bank profitability. In addition the efficiency scores were separately interpreted and analysed.